2019
DOI: 10.1016/j.vas.2019.100058
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of antibiotic use in global pig production: A systematic review

Abstract: Highlights Many classes of antibiotic used for humans are also used in food animals, including the highest priority of the critically important antimicrobials for human medicine in the World Health Organisation's list. Penicillins and Tetracyclines classes were the most commonly used antibiotics in many countries. Improve understanding of the use of antibiotics and factors influencing antibiotic use will help promoting prudent use of antimicrobials in live… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
247
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 256 publications
(262 citation statements)
references
References 50 publications
12
247
1
2
Order By: Relevance
“…Interestingly, the European Surveillance of Veterinary Antimicrobial Consumption (ESVAC) report on sales of veterinary antimicrobials agents in the EU in 2017 shows that penicillins and tetracyclines were the most frequently sold classes of antimicrobials per PCU in Italy [15], which is in line with our data. These substances are often used to treat respiratory diseases in fattening pigs [19,20], while lincosamides are frequently used in the treatment of common infections in Italy such as Brachyspira hyodysenteriae [18], Mycoplasma hyopneumoniae [21], and Lawsonia intracellularis [22] infections.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, the European Surveillance of Veterinary Antimicrobial Consumption (ESVAC) report on sales of veterinary antimicrobials agents in the EU in 2017 shows that penicillins and tetracyclines were the most frequently sold classes of antimicrobials per PCU in Italy [15], which is in line with our data. These substances are often used to treat respiratory diseases in fattening pigs [19,20], while lincosamides are frequently used in the treatment of common infections in Italy such as Brachyspira hyodysenteriae [18], Mycoplasma hyopneumoniae [21], and Lawsonia intracellularis [22] infections.…”
Section: Discussionmentioning
confidence: 99%
“…Acknowledging such significant associations in other species/production systems can be challenging, since several factors need to be taken into account. Moreover, prescribing habits of AMU might not be necessarily rational [20]. In the fattening pig sector, antimicrobials are mass-administered mainly via medicated feed or drinking water, while individual treatments are far less frequent [19].…”
Section: Discussionmentioning
confidence: 99%
“…These toxins trigger an intracellular signaling cascade resulting in the hypersecretion of electrolytes and water into the intestinal lumen, leading to watery diarrhea (Heo et al, 2013). Lekagul et al (2019) reported that the prophylactic use of in-feed antimicrobials, although strongly discouraged, remains a common practice for coping with PWD in some countries.…”
Section: Introductionmentioning
confidence: 99%
“…A range of antimicrobials are used in the treatment of sick animals, administered by food and/or water, or individually dosed by injection and orally [6,7]. Although the use of antimicrobials has benefits and can significantly improve welfare and decrease the mortality rates in pigs, their excessive and inappropriate use has become a concern because of the emergence and rise of antimicrobial resistance (AMR) in animals and humans, promoting measures to control and decrease antimicrobial use in livestock [8,9].…”
Section: Introductionmentioning
confidence: 99%